Motivational drivers of costly information search - Mamakos, Michalis; Bodenhausen, Galen V. (Cognition, 2024)
Acquiring information that aids decision-making is subject to a trade-off of accuracy versus cost, given that time, effort, or money are required to obtain decision-relevant information. Three studies (N = 2010) investigated the motivational dynamics shaping the priorities that govern this trade-off. Motivational orientations related to both the decision-making process and its outcome were examined. Regulatory focus theory describes two broad orientations to goal pursuit: promotion focus, prioritizing eager achievement, versus prevention focus, prioritizing vigilant security. We hypothesized that when the framing of a decision-making task activates a prevention focus rather than a promotion focus, individuals would be more willing to assume the costs of acquiring additional information before making their decisions. To test this hypothesis, participants made incentivized decisions with the option of acquiring additional information before making a final decision; importantly, obtaining this information incurred financial costs. Results consistently confirmed that prevention-focused decision makers were indeed more willing to assume the costs of acquiring additional information than promotion-focused individuals. The first two studies involved a scenario where participants were indifferent to the specific outcome of the decision process; accuracy was their only concern. In the final study, searchable, accuracy-enhancing information was also related to decision makers' partisan political preferences. Regulatory focus and the preference for partisan-congenial information were observed to be co-occurring but functionally orthogonal drivers of costly information search. Thus, prevention-framed messages can motivate the search for decision-relevant information, even when this search is costly and could lead to disagreeable data.